Translation Methods Used in Preface of English Textbook - Fikri, Abdul; Roza, Veni (Jambura Journal of English Teaching and Literature, 2024)
Translation plays a vital role in modern world. By the aid translation, people are able to overcome communication boundaries. Translating English textbook is one of the applications of translation. This research is descriptive qualitative research which aims to describe translation methods used by author in translating preface of Work in Progress English textbook. The researcher classified the data by using the theory of Newmark, (1988) which divided translation method into eight categories. This research reveals that the translation methods used in translating English textbook are free, semantic, faithful, communicative, and literal translation. The highest frequency of translation method used by the author in translating preface is free and semantic translation. The lowest frequency is literal translation.